Decrease in Trauma Admissions with COVID-19 Pandemic - Tovy H. Kamine; Adam Rembisz; Rebecca J. Barron; Carey Baldwin; Mark Kromer (Western Journal of Emergency Medicine, 2020)
Introduction: The COVID-19 pandemic has led to social distancing and decreased travel in the United States. The impact of these interventions on trauma and emergency general surgery patient volume has not yet been described. Methods: We compared trauma admissions and emergency general surgery (EGS) cases between February 1–April 14 from 2017–2020 in five two-week time periods. Data were compared across time periods with Poisson regression analysis. Results: There were significant decreases in overall trauma admissions (57.4% decrease, p<0.001); motor vehicle collisions (MVC) (80.5% decrease, p<0.001); and non-MVCs (45.1% decrease, p<0.001) from February–April 2020. We found no significant change in EGS cases (p = 0.70). Nor was there was a significant change in trauma cases in any other year 2017–2019. Conclusion: The COVID-19 pandemic’s burden of disease correlated with a significant decrease in trauma admissions, with MVCs experiencing a larger decrease than non-MVCs.